Characterization of a 7 kDa pollen allergen belonging to the gibberellin‐regulated protein family from three Cupressaceae species. Issue 8 (25th June 2020) - Ehrenberg, Angelica E.; Klingebiel, Caroline; Östling, Jonas; Larsson, Håkan; Mattsson, Lars; Vitte, Joana; Lidholm, Jonas
Abstract: Background: Severe allergy to fruits mediated by a 7 kDa allergen belonging to the gibberellin‐regulated protein (GRP) family is known to be associated with Cupressaceae pollinosis. Objective: To identify and characterize Cupressaceae pollen allergens involved in GRP‐related fruit allergy. Methods: Pru p 7‐related proteins from pollen of Cupressus sempervirens, Juniperus ashei and Cryptomeria japonica were identified using a rabbit anti‐Pru p 7 antiserum, purified chromatographically and sequenced by mass spectrometry and bioinformatic comparisons. The C sempervirens protein was produced as a recombinant allergen in Pichia pastoris . IgE antibody binding to pollen GRP proteins was analysed in a peach allergic (n = 54) and a cypress pollen allergic (n = 88) patient population from southern France using ImmunoCAP. Results: In each of the three Cupressaceae species studied, a 7 kDa pollen protein related to Pru p 7 was identified and found to comprise an amino acid sequence of 63 residues in length, 92%‐98% identical to each other and 67%‐68% identical to Pru p 7. The C sempervirens, J ashei and C japonica GRP allergens have been officially recognized by the WHO/IUIS Allergen Nomenclature Sub‐Committee and named Cup s 7, Jun a 7 and Cry j 7, respectively. Recombinant Cup s 7 showed IgE antibody binding capacity comparable to that of the purified natural allergen. Among 51 peach allergic subjects sensitized to Pru p 7, substantially higher levels of IgE to Cup s 7 than to Pru p 7 were found. Further, the pollen protein was able to completely outcompete IgE binding to Pru p 7, while the reverse competition effect was modest, consistent with primary sensitization by the pollen allergen. Conclusion and Clinical Relevance: Pru p 7‐related pollen allergens from three Cupressaceae species have been characterized and may become useful for the identification of pollinosis patients at risk of developing severe fruit allergy.